Designing an AHP methodology to prioritize critical elements for product innovation: An intellectual capital perspective - Ricardo Vergueiro Costa; Ana Paula Ramos (International Journal of Business Science & Applied Management (IJBSAM), 2015)
Intellectual capital has for the past decades been evidenced as an important source of competitive advantages and differentiation at the firm level. At the same time, innovation has become a critical factor for companies to ensure their sustainability and even their survival in a globalized business landscape. Having in mind these two crucial concepts for business success, this study intends to build on the relationships between intellectual capital and product innovation at the firm level. Specifically, we will design and test a model based on the Analytic Hierarchy Process, whose aim is to allow the prioritization of intellectual capital elements according to their relative importance for product innovation performance at the firm level. The main goal of this research is to build a diagnosis and action tool that helps business managers incorporate an intellectual capital perspective into their product innovation initiatives. This framework will help managers to better understand which intellectual capital elements are more critical to their product innovation efforts, and thereby systematize actions and clarify resource allocation priorities to improve their product innovation capabilities. In order to validate the practicability of this proposal, the methodology was empirically applied to a Portuguese innovative company.
Keywords: 650; intellectual capital; product innovation; Analytic Hierarchy Process; Portugal; AHP; SMEs